Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
"A burgeoning mega-club in the heart of Montreal's gay village, Sky embodies many forces active in gay club cultures and villages across North America at the end of the twentieth century. This project documents the daily operations of Sky–as a complex architectural site, a complicated set of managerial practices, and a popular space in Montreal's Village–and outlines the theoretical implications of such an establishment for both the gay community and for club culture more generally. A large entertainment complex currently undergoing a major expansion, Sky cannot be theorized as either a wholly oppressive or completely liberatory development. Although Sky presents some of the advantages of a mega-club for the gay community–increased diversity, accessibility and community–it also highlights the disadvantages in the development of such establishments: concentration of ownership, the removal of a gay presence from city streets, and the promotion of certain gay identities and cultures over others."